Medieval and Modern Water Management. An example from the excavation in Písek – Bakaláře-square (Southern Bohemia) - Houfková, Petra; Chytráček, M.; Jiřík, J.; Gruber, H; Kovačiková, Lenka; Michálek, J.; Sandner, R.; Pták, Martin; Schmotz, K.; Šálková, Tereza (Verlag Marie Leidorf, 2013)
This article provides new evidence for water management in the area of the Bakaláře-square in Písek (southern Bohemia). The Latin School in this area is dated to the early modern period, however, its medieval predecessor is indirectly known from written sources at least from the 15th century. If so far it remains uncertain whether there was continuity in the location of the school, some hints favouring this possibility should be taken into account.
Keywords: Medieval; Modern; Water Management; Písek